Penggunaan Handphone Pada Remaja Terhadap Interaksi Sosial - Arfan suryadi; Galuh Alif Ranchman; Ressa putri Amelia; Tiara citra rahayu (IHSA Institute, 2021)
In the current era of globalization where changes in technology and the flow of information are increasingly advanced and fast encouraging people to better understand the sophistication of technology Mobile is a two-way electronic telecommunication tool that can be carried everywhere and has the ability to send messages in the form of voice, picture, video and video messages. etc . Mobile phones can also change family life, work environment, school, friendship, religious activities, politics, and so on are all affected by communication technology. Positive influences include facilitating communication even though they are far away, making it easier to find information and so on. While the negative effects generated by the use of cellphones include the dangers resulting from using cellphones too often, teenagers are more likely to prefer communicating through the media rather than communicating face-to-face directly.